Quality Control Analysis of UD. Tiga Putra Crackers Product Using the Six Sigma Method and Failure Mode and Effect Analysisi (FMEA): Analisa Pengendalian Kualitas Kerupuk Ikan UD. Tiga Putra Menggunakan Metode Six Sigma dan Failure Mode and Effect Analysis (FMEA) - Eka Ayuning Agustin; Hana Catur Wahyuni (Academia Open, 2023)
UD. Tiga Putra is an industry engaged in cracker processing. There are product defects in the UD cracker production process. Tiga Putra so that it has an impact on the order rate from 50% to 30%. The purpose of the study is to determine the level of product defects with the highest risk level of failure that occurs and an improvement is made. The method used is the six sigma method and FMEA. The results of this study indicate an average DPMO value of 10848.08, a sigma value of 3.80 with the highest defect value of 41.1% in the type of crumbling defect. To get the best quality results, improvements can be made by performing maintenance and supervision on every aspect or factor that allows failure. Improvements can minimize defects and can increase company productivity so that it can be said that the company has achieved the desired target. Highlights : Utilizing Six Sigma Method and FMEA: Implementing these methodologies ensures a systematic approach to identifying and addressing product defects. Focus on High-Risk Areas: Prioritize improvement efforts based on the identified highest-risk failure types, such as crumbling defects, to maximize quality enhancement. Continuous Improvement Culture: By integrating maintenance and supervision across all factors contributing to failures, the company fosters a culture of ongoing improvement, ultimately enhancing productivity and achieving set targets. Keywords: Six Sigma, FMEA, Product Defects, Improvement, Quality Results